Low-viscosity composite rubber asphalt

Through the combination of carbonized bamboo powder and gelatinized material, the problem of softening of low-viscosity composite rubber asphalt at high temperatures is solved, and its high-temperature resistance and road bearing capacity are significantly improved, and it is suitable for a wide range of applications.

CN119286270AInactive Publication Date: 2025-01-10KUNMING SHUOXIANG ENGINEERING TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411641529.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing low-viscosity composite rubber asphalt is easy to soften in high-temperature environments, affecting the road bearing capacity, and the existing technology is difficult to effectively improve its high-temperature resistance.

Method used

Use discarded bamboo chopsticks as raw materials and are carbonized and crushed to make carbonized bamboo powder. The corrosion of sodium hydroxide solution and carbon dioxide activation gas treatment will increase the number of micropores and pore structure of bamboo fibers, and prepare gelatinized materials with corn starch. Add to rubber asphalt to improve its thermal radiation and heat dissipation properties.

Benefits of technology

The high temperature resistance of rubber asphalt is significantly improved, the softening in high temperature environment is avoided, the road bearing capacity is enhanced, and the application effect of additive materials is improved through the adhesion of gelatinized materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286270A_ABST
    Figure CN119286270A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of rubber asphalt, in particular to low-viscosity composite rubber asphalt. The low-viscosity composite rubber asphalt is prepared from the following raw materials in parts by weight: 80-100 parts of matrix asphalt, 20-30 parts of tire rubber powder, 10-15 parts of an additive, 8-10 parts of a gelatinization material, 8-10 parts of petroleum resin, 2-4 parts of a stabilizer and 2-4 parts of an activating agent, according to the invention, the bamboo material after carbonization treatment has a high ignition point and can be stably used after addition preparation and asphalt laying, the number of micropores in bamboo fibers is increased after carbonization, and after the bamboo material is added into the preparation process of rubber asphalt, the excellent thermal radiation performance and rich pore structure of carbonized bamboo powder are utilized to improve the thermal radiation performance of the rubber asphalt. The high-temperature-resistant rubber asphalt can effectively transfer heat to the surrounding environment in a radiation mode, meanwhile, abundant pores can help heat dissipation, the high-temperature-resistant performance of the rubber asphalt is improved, and the situation that the rubber asphalt is softened in the high-temperature environment and influences the bearing capacity of a road surface is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber asphalt, in particular to a low-viscosity composite rubber asphalt. Background Art

[0002] Rubber asphalt is made by first processing the raw materials of waste tires into rubber powder, then combining them in a certain coarse and fine grading ratio, adding a variety of high polymer modifiers, and fully melting and expanding with the base asphalt under high temperature conditions. With the enhancement of environmental awareness and the continuous advancement of waste tire processing technology, the application prospects of rubber asphalt are becoming more and more broad.

[0003] In the prior art, low-viscosity composite rubber asphalt is usually used for the convenience of paving during use. However, during the use of the rubber asphalt after paving, the road surface temperature will be high in summer. The high temperature will cause the rubber asphalt to soften and flow, affecting the bearing capacity of the asphalt paved road. Based on this, the present invention provides a low-viscosity composite rubber asphalt. Summary of the invention

[0004] The purpose of the present invention is to provide a low-viscosity composite rubber asphalt. The low-viscosity composite rubber asphalt prepared by the present invention not only has good high temperature resistance, but also has excellent viscosity performance, which effectively improves the use effect of the low-viscosity composite rubber asphalt.

[0005] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a low-viscosity composite rubber asphalt, characterized in that it is composed of the following raw materials in parts by weight: 80-100 parts of base asphalt, 20-30 parts of tire rubber powder, 10-15 parts of additives, 8-10 parts of gelatinized material, 8-10 parts of petroleum resin, 2-4 parts of stabilizer and 2-4 parts of activator.

[0006] Furthermore, the matrix asphalt is selected from any one of petroleum asphalt, coal tar asphalt, and shale asphalt.

[0007] Furthermore, the tire rubber powder uses waste tires as raw materials. After the waste tires are pre-treated and crushed, the steel wires are removed and the tires are crushed into coarse particles. The coarse particles are then sent to a grinding machine for grinding to obtain rubber powder.

[0008] Furthermore, the additive is prepared by the following method: S1: Select discarded bamboo chopsticks as raw materials, soak the discarded bamboo chopsticks in clean water for 6 to 10 hours, the mass of the clean water is 5 times that of the discarded bamboo chopsticks, add sodium hydroxide solution with a mass ratio of 6 to 8% of the clean water during the soaking process, stir and mix, rinse repeatedly 3 to 6 times after soaking, drain the water after rinsing, put into the oven, set at 60 to 70°C, treat for 2 to 4 hours, and obtain preliminary raw materials for standby use; S2: putting the preliminary raw material obtained in step S1 into a carbonization furnace, setting the temperature to continuously rise to 700-800°C to complete carbonization, the heating time is 2-3 hours, and taking it out after cooling to obtain carbonized bamboo chopsticks; S3: The carbonized bamboo chopsticks obtained in step S2 are washed with deionized water, and then placed in an oven at 70-80° C. for 4-6 hours. After drying, the carbonized bamboo chopsticks are dried; S4: The carbonized bamboo chopsticks obtained in step S3 are crushed into small pieces, and then sent into a planetary ball mill. After the ball milling, the pieces are sieved using a 100-mesh sieve to obtain an additive.

[0009] Furthermore, during the carbonization treatment process of step S2, carbon dioxide is introduced into the carbonization furnace, and the gas is introduced into the furnace at 300° C. for 15 to 20 minutes.

[0010] Furthermore, in step S4, the planetary ball mill is set to rotate at a speed of 280 to 320 r / min, and the ball milling time is 4 to 6 min.

[0011] Furthermore, the gelatinized material is prepared by the following method: corn starch and water are mixed, the mass ratio of corn starch to water is 1:10, the mixture is heated to 90-95°C, after heating, it is waited to cool to room temperature, zinc chloride solution is dripped into it, the mass of zinc chloride solution is 8-10% of corn starch, after stirring and mixing, it is allowed to react for 2-3 hours, then the temperature is raised to 80-85°C, and after drying, grinding and sieving, the gelatinized material is obtained.

[0012] Furthermore, in the process of preparing the low-viscosity composite rubber asphalt, the tire rubber powder, additives and gelatinized materials are processed separately to obtain a mixture.

[0013] Furthermore, the mixture is prepared by the following method: weighing tire rubber powder and additives as needed and adding them into a mixing device, setting medium-low speed mixing for 5 to 10 minutes, then adding gelatinized material and continuing mixing for 2 to 5 minutes. After the mixing is completed, the mixture is sent to a hot press, the hot press is preheated to 150°C, and hot pressed at a pressure of 4 to 6 MPa for 2 to 3 minutes. After taking out, it is cut into small pieces, ground and sieved to obtain the mixture.

[0014] Further, the following method is used for preparation: Step 1: Weigh the base asphalt as needed and heat it to 140°C until the base asphalt becomes fluid. Use a stirring device to set the speed to 400-600r / min to continuously stir the base asphalt, and raise the temperature to 170-180°C during the stirring process; Step 2: Weigh the mixture as needed and add it to the base asphalt, adjust the speed to 1500-1800r / min, then add petroleum resin and activator, stop stirring after completely mixing, and let it stand for 2-3h; Step 3: Use a high-speed shear emulsifier to shear the raw materials in step 2 for 25 to 30 minutes at a shear rate of 3500 to 4000 r / min. After the shearing is completed, add a stabilizer and set the stirring speed to 700 to 900 r / min. During the stirring process, keep the temperature at 180°C for 40 to 50 minutes. After the stirring is completed, a low-viscosity composite rubber asphalt is obtained.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention prepares additives by using discarded bamboo chopsticks as raw materials. After the discarded bamboo chopsticks are carbonized and crushed, carbonized bamboo powder is made. The bamboo material after carbonization has a higher ignition point and can be used more stably after additive preparation and asphalt paving. The number of micropores in the bamboo fiber is increased after carbonization. After being added to the preparation process of rubber asphalt, the excellent thermal radiation performance and rich pore structure of the carbonized bamboo powder can be used to effectively transfer heat to the surrounding environment in a radiation manner. At the same time, the presence of rich pores can help dissipate heat, thereby improving the high temperature resistance of rubber asphalt and preventing the rubber asphalt from softening in a high temperature environment and affecting the bearing capacity of the road surface.

[0016] 2. The present invention adds sodium hydroxide solution in the step of processing discarded bamboo chopsticks. Sodium hydroxide is an alkaline solution with corrosive effect. After contacting with the bamboo chopsticks, it can corrode the surface of the bamboo chopsticks. After cleaning, a large number of pits can be formed on the surface of the bamboo chopsticks. In the subsequent carbonization treatment, it can ensure that the bamboo chopsticks are heated evenly, thereby improving the expansion efficiency of the micropores inside the bamboo chopsticks, thereby improving the effect of the additive on improving the high temperature resistance of rubber asphalt.

[0017] 3. The present invention introduces carbon dioxide during the carbonization process. After the introduction, carbon dioxide acts as an activation gas to activate the formation of bamboo charcoal pores, assist in the formation of bamboo charcoal pore structure, enrich the pore structure, and further improve the heat dissipation performance of the additive. By adding gelatinized material to the rubber asphalt preparation process, the carbohydrates in the gelatinized material can have a better adhesion effect after contacting with tire rubber powder during the preparation process, thereby improving the use effect of the additive. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 A rubber asphalt preparation flow chart of a low-viscosity composite rubber asphalt is proposed for the invention; Figure 2 The invention proposes a flow chart for preparing a mixture of low-viscosity composite rubber asphalt. DETAILED DESCRIPTION

[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.

[0021] The present embodiment provides a low-viscosity composite rubber asphalt, which is characterized by being composed of the following raw materials in parts by weight: 80 to 100 parts of base asphalt, 20 to 30 parts of tire rubber powder, 10 to 15 parts of additives, 8 to 10 parts of gelatinized material, 8 to 10 parts of petroleum resin, 2 to 4 parts of stabilizer and 2 to 4 parts of activator.

[0022] In some embodiments, the base asphalt is selected from any one of petroleum asphalt, coal tar asphalt, and shale asphalt.

[0023] In some embodiments, tire rubber powder uses waste tires as raw materials. After the waste tires are pre-treated and crushed, the steel wires are removed and the tires are crushed into coarse particles. The coarse particles are then sent to a grinding mill for grinding to obtain rubber powder.

[0024] In some embodiments, the additive is prepared by the following method: S1: Select discarded bamboo chopsticks as raw materials, soak the discarded bamboo chopsticks in clean water for 6 to 10 hours, the mass of the clean water is 5 times that of the discarded bamboo chopsticks, add sodium hydroxide solution with a mass ratio of 6 to 8% of the clean water during the soaking process, stir and mix, rinse repeatedly 3 to 6 times after soaking, drain the water after rinsing, put into the oven, set at 60 to 70°C, treat for 2 to 4 hours, and obtain preliminary raw materials for standby use; By adding sodium hydroxide solution in the processing step of discarded bamboo chopsticks, sodium hydroxide is an alkaline solution with corrosive effect. After contacting with the bamboo chopsticks, it can corrode the surface of the bamboo chopsticks. After cleaning, a large number of pits can be formed on the surface of the bamboo chopsticks. In the subsequent carbonization treatment, it can ensure that the bamboo chopsticks are heated evenly, thereby improving the expansion efficiency of the micropores inside the bamboo chopsticks, thereby improving the effect of the additive on improving the high temperature resistance of rubber asphalt.

[0025] S2: putting the preliminary raw material obtained in step S1 into a carbonization furnace, setting the temperature to continuously rise to 700-800°C to complete carbonization, the heating time is 2-3 hours, and taking it out after cooling to obtain carbonized bamboo chopsticks; S3: The carbonized bamboo chopsticks obtained in step S2 are washed with deionized water, and then placed in an oven at 70-80° C. for 4-6 hours. After drying, the carbonized bamboo chopsticks are dried; S4: The carbonized bamboo chopsticks obtained in step S3 are crushed into small pieces, and then sent into a planetary ball mill. After the ball milling, the pieces are sieved using a 100-mesh sieve to obtain an additive.

[0026] In this embodiment, the bamboo material after carbonization has a higher ignition point and can be used more stably after adding preparation and asphalt paving. The number of micropores in the bamboo fiber is increased after carbonization. After being added to the preparation process of rubber asphalt, the excellent thermal radiation performance and rich pore structure of the carbonized bamboo powder can be used to effectively transfer heat to the surrounding environment in a radiation manner. At the same time, the presence of rich pores can help dissipate heat, thereby improving the high temperature resistance of rubber asphalt and preventing the softening of rubber asphalt in high temperature environment from affecting the bearing capacity of the road surface.

[0027] In some embodiments, during the carbonization process of step S2, carbon dioxide is introduced into the carbonization furnace. The gas is introduced into the furnace at 300° C. for 15 to 20 minutes.

[0028] In this embodiment, by introducing carbon dioxide during the carbonization process, carbon dioxide acts as an activation gas after introduction, which can activate the formation of bamboo charcoal pores, assist in the formation of bamboo charcoal pore structure, enrich the pore structure, and further enhance the heat dissipation performance of the additive.

[0029] In some embodiments, in step S4, the planetary ball mill is set to rotate at a speed of 280 to 320 r / min, and the ball milling time is 4 to 6 min.

[0030] In some embodiments, the gelatinized material is prepared by the following method: corn starch and water are mixed, the mass ratio of corn starch to water is 1:10, the mixture is heated to 90-95°C, after heating, wait for it to cool to room temperature, and then drop a zinc chloride solution, the mass of the zinc chloride solution is 8-10% of the corn starch, after stirring and mixing, let it stand to react for 2-3 hours, then heat it to 80-85°C, and after drying, grinding, and sieving, a gelatinized material is obtained.

[0031] In this embodiment, by adding gelatinized material to the rubber asphalt preparation process, the carbohydrates in the gelatinized material can play a good adhesion role after contacting with tire rubber powder during the preparation process, thereby improving the use effect of the additive.

[0032] In some embodiments, during the preparation of low-viscosity composite rubber asphalt, tire rubber powder, additives and gelatinized materials are processed separately to obtain a mixture.

[0033] In this embodiment, the mixture is used as the raw material to be mixed with the base asphalt in the first step. After the base asphalt is initially heated, the base asphalt has strong fluidity. At this time, the mixture is added and stirred to mix more evenly, thereby improving the distribution uniformity of the mixture in the rubber asphalt.

[0034] In some embodiments, the mixture is prepared by the following method: weigh tire rubber powder and additives as needed and add them to a mixing device, set the medium-low speed to mix for 5 to 10 minutes, then add the gelatinized material and continue mixing for 2 to 5 minutes. After the mixing is completed, send it into a hot press, preheat the hot press to 150°C, set the pressure to 4 to 6 MPa for hot pressing for 2 to 3 minutes, take it out, cut it into small pieces, grind and sieve it to obtain the mixture.

[0035] In some embodiments, the following method is used: Step 1: Weigh the base asphalt as needed and heat it to 140°C until the base asphalt becomes fluid. Use a stirring device to set the speed to 400-600r / min to continuously stir the base asphalt, and raise the temperature to 170-180°C during the stirring process; Step 2: Weigh the mixture as needed and add it to the base asphalt, adjust the speed to 1500-1800r / min, then add petroleum resin and activator, stop stirring after completely mixing, and let it stand for 2-3h; Step 3: Use a high-speed shear emulsifier to shear the raw materials in step 2 for 25 to 30 minutes at a shear rate of 3500 to 4000 r / min. After the shearing is completed, add a stabilizer and set the stirring speed to 700 to 900 r / min. During the stirring process, keep the temperature at 180°C for 40 to 50 minutes. After the stirring is completed, a low-viscosity composite rubber asphalt is obtained.

[0036] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.

[0037] Experiment 1: The following raw materials were used in parts by weight: 80 parts of base asphalt, 20 parts of tire rubber powder, 10 parts of additives, 8 parts of gelatinized material, 8 parts of petroleum resin, 2 parts of stabilizer and 2 parts of activator; The base asphalt is petroleum asphalt; Preparation of additives: Soak discarded bamboo chopsticks in clean water for 6 hours, the mass of clean water is 5 times that of discarded bamboo chopsticks, add sodium hydroxide solution with a mass of 6% of clean water during the soaking process, stir and mix, rinse repeatedly 3 times after soaking, drain the water after rinsing, put into an oven, set 60°C, treat for 2 hours, and obtain preliminary raw materials, put the preliminary raw materials into a carbonization furnace, set the temperature to continuously rise to 700°C to complete carbonization, the heating time is 2 hours, take out after cooling, and obtain carbonized bamboo chopsticks, during the carbonization process, introduce carbon dioxide into the carbonization furnace, the gas is introduced at 300°C in the furnace, the introduction time is 15 minutes, the carbonized bamboo chopsticks are washed with deionized water, and then placed in an oven, set 70°C, and treated for 4 hours, after drying, the carbonized bamboo chopsticks are broken into small pieces, and then sent to a planetary ball mill, the planetary ball mill is set to a speed of 280r / min, the ball milling time is 4 minutes, and after the ball milling is completed, a 100-mesh sieve is used to sieve to obtain additives; The gelatinized material is prepared by mixing corn starch and water in a mass ratio of 1:10, heating the mixture to 90°C, waiting for the mixture to cool to room temperature, dropping a zinc chloride solution in an amount of 8% of the corn starch, stirring and mixing, and allowing the mixture to react for 2 hours, then heating the mixture to 80°C, drying, grinding, and sieving to obtain a gelatinized material; The mixture is prepared by weighing tire rubber powder and additives as needed and adding them into the mixing equipment, setting the medium-low speed to mix for 5 minutes, then adding the gelatinized material and continuing to mix for 2 minutes. After the mixing is completed, the mixture is sent to the hot press, which is preheated to 150°C and set to hot press at 4Mpa for 2 minutes. After taking out, it is cut into small pieces, ground and sieved to obtain the mixture; To prepare low-viscosity composite rubber asphalt: weigh the base asphalt as needed and heat it to 140°C until the base asphalt becomes fluid. Use a stirring device to set the speed to 400r / min to continuously stir the base asphalt. Heat the temperature to 170°C during stirring. Weigh the mixture as needed and add it to the base asphalt. Adjust the speed to 1500r / min, then add petroleum resin and activator. Stop stirring after complete mixing and let stand for 2h. Use a high-speed shear emulsifier to shear the raw materials for 25min at a shear rate of 3500r / min. After shearing, add a stabilizer and set stirring at 700r / min. Keep the temperature at 180°C for 40min during stirring. After stirring, low-viscosity composite rubber asphalt is obtained.

[0038] Experiment 2: The matrix asphalt is coal tar asphalt; Preparation of additives: Soak discarded bamboo chopsticks in clean water for 8 hours, the mass of clean water is 5 times that of discarded bamboo chopsticks, add sodium hydroxide solution accounting for 7% of the mass of clean water during the soaking process, stir and mix, rinse repeatedly 5 times after soaking, drain the water after rinsing, put into an oven, set 65°C, treat for 3 hours, and obtain preliminary raw materials, put the preliminary raw materials into a carbonization furnace, set the temperature to continuously rise to 750°C to complete carbonization, the heating time is 2.5 hours, take out after cooling, and obtain carbonized bamboo chopsticks, during the carbonization process, introduce carbon dioxide into the carbonization furnace, the gas is introduced into the furnace at 300°C, and the introduction time is 17 minutes, the carbonized bamboo chopsticks are washed with deionized water, and then placed in an oven, set 75°C, and treated for 5 hours, after drying, the carbonized bamboo chopsticks are broken into small pieces, and then sent to a planetary ball mill, the planetary ball mill is set to a speed of 300r / min, the ball milling time is 5 minutes, and after the ball milling is completed, a 100-mesh sieve is used to sieve to obtain additives; The gelatinized material is prepared by mixing corn starch and water in a mass ratio of 1:10, heating the mixture to 92°C, waiting for the mixture to cool to room temperature, dropping a zinc chloride solution in a mass of 9% of the corn starch, stirring and mixing, and allowing the mixture to react for 2.5 hours, then heating to 82°C, drying, grinding, and sieving to obtain a gelatinized material; The mixture is prepared by weighing tire rubber powder and additives as needed and adding them into the mixing equipment, setting the medium-low speed to mix for 7 minutes, then adding the gelatinized material and continuing to mix for 3 minutes. After the mixing is completed, the mixture is sent to the hot press, which is preheated to 150°C and set to hot press at 5Mpa for 2.5 minutes. After taking out, it is cut into small pieces, ground and sieved to obtain the mixture; To prepare low-viscosity composite rubber asphalt: weigh the base asphalt as needed and heat it to 140°C until the base asphalt becomes fluid. Use a stirring device to set the speed to 500r / min to continuously stir the base asphalt. Heat it to 175°C during stirring. Weigh the mixture as needed and add it to the base asphalt. Adjust the speed to 1650r / min, then add petroleum resin and activator. End stirring after complete mixing, let it stand for 2.5h, use a high-speed shear emulsifier to shear the raw materials in step 2 for 27min at a shear rate of 3700r / min. After shearing, add a stabilizer and set stirring at 800r / min. Keep the temperature at 180°C for 45min during stirring. After stirring, low-viscosity composite rubber asphalt is obtained.

[0039] Experiment 3: The matrix asphalt is shale asphalt; Preparation of additives: Soak discarded bamboo chopsticks in clean water for 10 hours, the mass of clean water is 5 times that of discarded bamboo chopsticks, add sodium hydroxide solution with a mass of 8% of clean water during the soaking process, stir and mix, rinse repeatedly 6 times after soaking, drain the water after rinsing, put into an oven, set 70°C, treat for 4 hours, and obtain preliminary raw materials, put the preliminary raw materials into a carbonization furnace, set the temperature to continuously rise to 800°C to complete carbonization, the heating time is 3 hours, take out after cooling, and obtain carbonized bamboo chopsticks, during the carbonization process, introduce carbon dioxide into the carbonization furnace, the gas is introduced into the furnace at 300°C, the introduction time is 20 minutes, the carbonized bamboo chopsticks are washed with deionized water, and then placed in an oven, set 80°C, and treated for 6 hours, after drying, the carbonized bamboo chopsticks are broken into small pieces, and then sent to a planetary ball mill, the planetary ball mill is set to a speed of 320r / min, the ball milling time is 6 minutes, and after the ball milling is completed, a 100-mesh sieve is used to sieve to obtain additives; The gelatinized material is prepared by mixing corn starch and water in a mass ratio of 1:10, heating the mixture to 95°C, waiting for the mixture to cool to room temperature, dropping a zinc chloride solution in a mass of 10% of the corn starch, stirring and mixing, and allowing the mixture to react for 3 hours, then heating to 85°C, drying, grinding, and sieving to obtain a gelatinized material; The mixture is prepared by weighing tire rubber powder and additives as needed and adding them into the mixing equipment, setting the medium-low speed to mix for 10 minutes, then adding the gelatinized material and continuing to mix for 5 minutes. After the mixing is completed, the mixture is sent to the hot press, which is preheated to 150°C and set to hot press at 6Mpa for 3 minutes. After taking out, it is cut into small pieces, ground and sieved to obtain the mixture; To prepare low-viscosity composite rubber asphalt: weigh the base asphalt as needed and heat it to 140°C until the base asphalt becomes fluid. Use a stirring device to set the speed to 600r / min to continuously stir the base asphalt. Heat it to 180°C during stirring. Weigh the mixture as needed and add it to the base asphalt. Adjust the speed to 1800r / min, then add petroleum resin and activator. End stirring after complete mixing and let stand for 3h. Use a high-speed shear emulsifier to shear the raw materials in step 2 for 30min at a shear rate of 4000r / min. After shearing, add a stabilizer and set stirring at 900r / min. Keep the temperature at 180°C for 50min during stirring. After stirring, low-viscosity composite rubber asphalt is obtained.

[0040] Comparative Example 1: The difference between this comparative example and Experiment 1 is that: This comparative example does not contain any additives.

[0041] Comparative Example 2: The difference between this comparative example and Experiment 1 is that: This comparative example does not contain gelling material.

[0042] Comparative Example 3: The difference between this comparative example and Experiment 1 is that: In this comparative example, no sodium hydroxide solution was added when preparing the additive.

[0043] Comparative Example 4: The difference between this comparative example and Experiment 1 is that: In this comparative example, no carbon dioxide was introduced into the carbonization furnace when preparing the additive.

[0044] Performance test: Performance test was carried out on the low viscosity composite rubber asphalt prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4.

[0045] In the performance test, the high temperature resistance test method is as follows: the low viscosity composite rubber asphalt prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are poured into the mold respectively, and left to stand for 48 hours at room temperature, and then the rubber asphalt in each mold is subjected to a high temperature resistance test, and the rubber asphalt is heated at a heating rate of 5°C / min, and the temperature and state of the rubber asphalt are monitored in real time during the heating process; The viscosity test method is: use the test method in JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" to test the viscosity of asphalt at room temperature.

[0046] The test data obtained are recorded in the following table:

[0047] It can be seen that the softening point temperature of the rubber asphalt prepared in Comparative Examples 1, 2, 3 and 4 is lower than that in Experiments 1, 2 and 3, and the viscosity of the rubber asphalt prepared in Comparative Examples 1, 2, 3 and 4 is higher than that in Experiments 1, 2 and 3. This shows that: the additive is prepared by using discarded bamboo chopsticks as raw materials, and the discarded bamboo chopsticks are carbonized and crushed to make carbonized bamboo powder. The bamboo material after carbonization has a higher ignition point and can be used more stably after the addition preparation and asphalt paving. The number of micropores in the bamboo fiber is increased after carbonization. After being added to the preparation process of rubber asphalt, the excellent thermal radiation performance and rich pore structure of the carbonized bamboo powder can be used to effectively transfer heat to the surrounding environment by radiation. At the same time, the presence of rich pores can help dissipate heat, thereby improving the high temperature resistance of rubber asphalt.

[0048] By comparing and analyzing the relevant data in the table, it can be seen that the low-viscosity composite rubber asphalt prepared by the present invention not only has good high temperature resistance, but also has low viscosity. This shows that the low-viscosity composite rubber asphalt provided by the present invention has a broader market prospect and is more suitable for promotion.

[0049] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0050] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A low-viscosity composite rubber asphalt, characterized in that: The invention is composed of the following raw materials in parts by weight: 80-100 parts of base asphalt, 20-30 parts of tire rubber powder, 10-15 parts of additives, 8-10 parts of gelatinized materials, 8-10 parts of petroleum resins, 2-4 parts of stabilizers and 2-4 parts of activators.

2. The low-viscosity composite rubber asphalt according to claim 1, characterized in that: The matrix asphalt is selected from any one of petroleum asphalt, coal tar asphalt and shale asphalt.

3. The low-viscosity composite rubber asphalt according to claim 1, characterized in that: The tire rubber powder uses waste tires as raw materials. After the waste tires are pre-treated and crushed, the steel wires are removed and the tires are crushed into coarse particles. The coarse particles are then sent to a grinding machine for grinding to obtain rubber powder.

4. The low-viscosity composite rubber asphalt according to claim 1, characterized in that: The additive is prepared by the following method: S1: Select discarded bamboo chopsticks as raw materials, soak the discarded bamboo chopsticks in clean water for 6 to 10 hours, the mass of the clean water is 5 times that of the discarded bamboo chopsticks, add sodium hydroxide solution with a mass ratio of 6 to 8% of the clean water during the soaking process, stir and mix, rinse repeatedly 3 to 6 times after soaking, drain the water after rinsing, put into the oven, set at 60 to 70°C, treat for 2 to 4 hours, and obtain preliminary raw materials for standby use; S2: putting the preliminary raw material obtained in step S1 into a carbonization furnace, setting the temperature to continuously rise to 700-800°C to complete carbonization, the heating time is 2-3 hours, and taking it out after cooling to obtain carbonized bamboo chopsticks; S3: The carbonized bamboo chopsticks obtained in step S2 are washed with deionized water, and then placed in an oven at 70-80° C. for 4-6 hours. After drying, the carbonized bamboo chopsticks are dried; S4: The carbonized bamboo chopsticks obtained in step S3 are crushed into small pieces, and then sent into a planetary ball mill. After the ball milling, the pieces are sieved using a 100-mesh sieve to obtain an additive.

5. The low-viscosity composite rubber asphalt according to claim 4, characterized in that: During the carbonization treatment process of step S2, carbon dioxide is introduced into the carbonization furnace. The gas is introduced into the furnace at 300° C. for 15 to 20 minutes.

6. The low-viscosity composite rubber asphalt according to claim 4, characterized in that: In step S4, the planetary ball mill is set to rotate at a speed of 280 to 320 r / min, and the ball milling time is 4 to 6 min.

7. The low-viscosity composite rubber asphalt according to claim 1, characterized in that: The gelatinized material is prepared by the following method: corn starch and water are mixed, the mass ratio of corn starch to water is 1:10, the mixture is heated to 90-95° C., after heating, the mixture is cooled to room temperature, zinc chloride solution is added dropwise, the mass of the zinc chloride solution is 8-10% of the corn starch, the mixture is stirred and allowed to react for 2-3 hours, and then the mixture is heated to 80-85° C., and the gelatinized material is obtained after drying, grinding and sieving.

8. The low-viscosity composite rubber asphalt according to claim 1, characterized in that: In the preparation process of the low-viscosity composite rubber asphalt, tire rubber powder, additives and gelatinized materials are processed separately to obtain a mixture.

9. The low-viscosity composite rubber asphalt according to claim 8, characterized in that: The mixture is prepared by the following method: weighing tire rubber powder and additives as needed and adding them into a mixing device, setting medium-low speed mixing for 5-10 minutes, then adding gelatinized material and continuing mixing for 2-5 minutes. After the mixing is completed, the mixture is sent to a hot press, the hot press is preheated to 150° C., and hot-pressed at a pressure of 4-6 MPa for 2-3 minutes. After taking out, it is cut into small pieces, ground and sieved to obtain the mixture.

10. The low-viscosity composite rubber asphalt according to claim 8, characterized in that: Prepared by the following method: Step 1: Weigh the base asphalt as needed and heat it to 140°C until the base asphalt becomes fluid. Use a stirring device to set the speed to 400-600r / min to continuously stir the base asphalt, and raise the temperature to 170-180°C during the stirring process; Step 2: Weigh the mixture as needed and add it to the base asphalt, adjust the speed to 1500-1800r / min, then add petroleum resin and activator, stop stirring after completely mixing, and let it stand for 2-3h; Step 3: Use a high-speed shear emulsifier to shear the raw materials in step 2 for 25 to 30 minutes at a shear rate of 3500 to 4000 r / min. After the shearing is completed, add a stabilizer and set the stirring speed to 700 to 900 r / min. During the stirring process, keep the temperature at 180°C for 40 to 50 minutes. After the stirring is completed, a low-viscosity composite rubber asphalt is obtained.

Citation Information

Cited By

  • High-temperature-resistant road asphalt and preparation method thereof

    CN120137417A